EXPRESSION OF EMOTION IN MIMIC MODE (Archive of Conferences, 2020)
According to semiotic theory, "the most important feature of signs is that their main function is to communicate between people and to receive and receive information." Among these features, the word is distinguished by its semantic-functional structure. It is clear that the essence of things and objects that exist in the objective world is perceived by man and is a synthesis of thinking.